MEKANISME DAN PERLAKUAN AKUNTANSI PEMBIAYAAN MURABAHAH KONSUMTIF (STUDI PADA PT BPR SYARIAH X) - Shalsabella, Irene (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2014)
The purpose of this research is to find out the financing mechanism and accounting behavior of murabahah consumptive at PT. BPR Syariah X. This research uses qualitative approach by using case study. The result of the research shows that PT. BPR Syariah X uses consumptive murabahah contract in distributing murabahah financing. Generally, accounting principles which have been implemented by the bank is in accordance with Accounting Standard Statement (PSAK) 102 about Murabahah. The selling price determination is based on cost of goods sold plus margin agreed by both parties. It should be noted that in murabahah context bank acts as a seller, the buyerâs handover is in the form of money not assets so the buyer can purchase by themselves, without additional contract like urbun or wakalah. Beside that, sales discount and penalty (taâzir) on the late payment has been agreed before or at the moment of contract in accordance with the bank policy. Further more, bank have directly collect to the costumer if the customer is not capable to pay their debt at current period. Keywords: Murabahah, National Board of Syariah, Accounting Standard Statement (PSAK) No. 102